Privatization and stock market liquidity - Bernardo Bortolotti; Frank de Jong; Giovanna Nicodano; Ibolya Schindele (Fondazione Eni Enrico Mattei (FEEM), 2002)
Share issue privatization - i.e. privatization on public equity markets - is often claimed to foster stock market development. In this paper, we provide an empirical assessment of this claim, testing the role of privatization on two market liquidity measures in a panel with monthly data of 19 developed economies. Privatization is shown to be key in improving domestic stock market liquidity, controlling for other economic, financial and institutional determinants. Results do not appear to be driven by reverse causality or non-stationarity of the data.
Keywords: L33; G14; 330; Privatization; Financial Market Development; Privatisierung; Börsengang; Aktienmarkt; Liquidität; Industriestaaten